Littoral Negotiations - Mouritz, Liam (2017)
This project explores the blurred interface between the land and the sea known as the littoral zone. The very matter from which this condition is constructed is wet sand or sediment. This is the material from which to begin and envisage alternative design scenarios for the littoral zone of the Mediterranean Sea. Parallel to this, the project envisions ways in which Architect’s agency could be enhanced and design can be a relevant tool for the production of littoral zones. Littoral Negotiations Project is presented here as a speculation of the role of the architect, the implementation of design and the potential outcomes it can have in the generation of alternative scenarios for a specific context and territory within the Mediterranean Sea.